2001
DOI: 10.1038/35074593
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-D, a new protease-activated growth factor

Abstract: Platelet-derived growth factor (PDGF) has been directly implicated in developmental and physiological processes, as well as in human cancer, fibrotic diseases and arteriosclerosis. The PDGF family currently consists of at least three gene products, PDGF-A, PDGF-B and PDGF-C, which selectively signal through two PDGF receptors (PDGFRs) to regulate diverse cellular functions. After two decades of searching, PDGF-A and B were the only ligands identified for PDGFRs. Recently, however, database mining has resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
260
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(269 citation statements)
references
References 20 publications
7
260
0
2
Order By: Relevance
“…This cleavage of the CUB domain results in the appearance of a 23-kd (PDGF-C) and a 32-kd (PDGF-D) protein under reducing conditions, representing the "core" growth factor domain monomers (2)(3)(4)25). Although the respective bands were usually absent in the case of PDGF-C, active PDGF-D could be detected in all SM samples investigated (at the predicted molecular mass of 32 kd) and showed a significantly higher expression in RA SM.…”
Section: Discussionmentioning
confidence: 99%
“…This cleavage of the CUB domain results in the appearance of a 23-kd (PDGF-C) and a 32-kd (PDGF-D) protein under reducing conditions, representing the "core" growth factor domain monomers (2)(3)(4)25). Although the respective bands were usually absent in the case of PDGF-C, active PDGF-D could be detected in all SM samples investigated (at the predicted molecular mass of 32 kd) and showed a significantly higher expression in RA SM.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these peptides require extracellular proteolytic cleavage to release the biologically active GFD (designated PDGF-CC and -DD). The GFD of PDGF-C and -D share significant homology with one another (approximately 50%) and with the previously described PDGF (20 to 23%) (7,8).…”
mentioning
confidence: 90%
“…The accepted paradigm for the last two decades has been that PDGF-A binds and signals only through PDGFR-␣␣, and PDGF-B can bind both PDGFR-␤␤ and PDGFR-␣/␤ (10 -12). It has now been shown that activated PDGF-CC can bind to both PDGFR-␣ and -␣/␤ (6,8), whereas PDGF-DD is the only known PDGFR-␤-specific ligand (7).…”
mentioning
confidence: 99%
“…However, when PDGF-C and PDGF-D were discovered, new insights into this growth factor family were gained (Li et al, 2000;Bergsten et al, 2001;LaRochelle et al, 2001). In addition to a conserved growth factor domain (GFD), shared by all four members, PDGF-C and PDGF-D contain an N-terminal CUB domain (Bork and Beckmann, 1993) within the full-length (fl) protein.…”
Section: Introductionmentioning
confidence: 99%